2019
DOI: 10.7150/ijbs.29689
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPK by metformin promotes renal cancer cell proliferation under glucose deprivation through its interaction with PKM2

Abstract: Metformin, a common therapeutics for type 2 diabetics, was recently demonstrated to possess antitumor activity in various cancer types. However, its therapy effect in renal cell carcinoma (RCC) still remains controversial. In this study, we found that metformin treatment in RCC cells lead to activation of AMPK, which suppressed the cell proliferation under normal condition, but enhanced cell proliferation under glucose deprivation (GD) condition. Depletion of AMPK by siRNA abolished the proliferation effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Deng et al . studied the antiproliferative antisurvival activity of metformin against six triple-negative breast cancer cell lines, and found that metformin induced growth inhibition on all of these cell lines [18].…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al . studied the antiproliferative antisurvival activity of metformin against six triple-negative breast cancer cell lines, and found that metformin induced growth inhibition on all of these cell lines [18].…”
Section: Resultsmentioning
confidence: 99%
“…3D). It has been proposed that metformin activates AMPK (38,40,42) and in agreement with this, wild type mice have increased phosphorylation of both AMPK and ACC upon metformin treatment. Surprisingly, metformin has the opposite effect in iMSUD mice (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…4A, Figure S4). Metformin has been shown to promote mitochondrial metabolism via regulation of redox state (33)(34)(35)(36)(37), activation of AMPK (38)(39)(40)(41)(42) and increased the production of lactate (43)(44)(45)(46). Here, metformin was unable to restore intra-tissue lactate or TCA metabolite levels in iMSUD mice unlike in wild type mice, suggesting that BCKDH function is required for metformin action (Fig.…”
Section: Global Dysfunction In Oxidative Carbon Metabolism Caused By mentioning
confidence: 92%
“…In agreement with these findings, increased AMPK/pAMPK expression is indicative of favorable survival in patients with carcinomas of the uterine cervix [10], ovary [11], and liver [12] whose tumor cells display cytoplasmic AMPK/pAMPK immunohistochemical (IHC) staining. Conversely, and paradoxically, nuclear pAMPK has been revealed to promote the survival, proliferation, and metastatic capacity of malignant cells under metabolic stress, likely through oncogene activation [13,14]. Recently, Liu et al [14] demonstrated that nuclear pAMPK mediates the proliferation of glucose-deprived human renal cell carcinoma cells, by recruiting pyruvate kinase isozymes M2 and β-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, and paradoxically, nuclear pAMPK has been revealed to promote the survival, proliferation, and metastatic capacity of malignant cells under metabolic stress, likely through oncogene activation [13,14]. Recently, Liu et al [14] demonstrated that nuclear pAMPK mediates the proliferation of glucose-deprived human renal cell carcinoma cells, by recruiting pyruvate kinase isozymes M2 and β-catenin. Although analysis from ccRCC tumor lysates revealed that increased AMPK mRNA and pAMPK are associated with favorable outcomes [1,6], the prognostic significance of pAMPK subcellular location has not yet been investigated in patients with ccRCC.…”
Section: Introductionmentioning
confidence: 99%